Strategies towards the synthesis of anti-tuberculosis drugs. Issue 22 (21st May 2019) - Rode, Haridas B.; Lade, Dhanaji M.; Grée, René; Mainkar, Prathama S.; Chandrasekhar, Srivari
Abstract : In this report, we reviewed the strategies towards the synthesis of anti-tuberculosis drugs. They include semisynthetic approaches, resolution based strategies, microbial transformations, solid phase synthesis, and asymmetric synthesis. Abstract : Antituberculosis drugs have captured the attention of the scientific community due to the emergence of drug resistance. Hence, the development of new analogs and new drugs which can treat drug-resistant tuberculosis is required. In this report, we reviewed the strategies towards the synthesis of antituberculosis drugs. These strategies include semisynthetic approaches, resolution based strategies, microbial transformations, solid phase synthesis, and asymmetric synthesis. As stereochemistry is an important hallmark of many drugs, the strategies based on asymmetric synthesis are described in detail. The emphasis on semisynthetic approaches is given for aminoglycoside antibiotics.